Pendidikan Toleransi Pada Anak Keluarga Muslim Minoritas Dusun Kandangsari Desa Mororejo Kabupaten Pasuruan - Askhabul Kirom (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2021)
Family is the first place for children. In the family, the child first gets the influence of values. Therefore, the family is encouraged as a foundation for children to be more open, tolerant, and democratic. the author uses a qualitative research type with a phenomenological approach, the data collection techniques used include; interviews, observations, documents, determination of data sources by purposive sampling, snowball sampling, data analysis using phenomenological forms. The results showed that tolerance education for the children of the Kandangsari hamlet family, whether Muslim or Hindu, worked together as a community and community service without discrimination on the basis of religion, the children gathered to all their friends who were fully aware of being tolerant in accepting all differences, whether religion, religion or religion. as well as culture.